Steam Distillation and Gas Chromatographic Analysis of Volatile Components of Zingiber Officinale - A. Akpanika, Grace; E. Nkanor , Effiong; A. Ayoola, Gloria (Nigerian Journal of Pharmaceutical and Applied Science Research, 2021)
Background: The use of ginger in aromatherapy and humidification has become a common practice since the advent of Covid-19 pandemic. Even though ginger will not prevent or cure Covid-19 and other viral infections, there are evidences that ginger can give relief from nausea, cough, nasal irritation, fatigue and aches. Methods: The oil of Zingiber officinale (ginger) from Calabar metropolis was extracted using steam distillation. Gas chromatography Mass Spectrometry was used to determine volatile compounds. Results: 57 compounds were identified, Zingiberene (26.85%) being the most abundant. Other compounds identified included Sesquiphillandrene (22.12%), Curcumene (10.69%), Eucalyptus (2.80%), Eugenol (2.70%), B-Phellandrene (1.65%), Bisabollene (1.52%), Pinene (0.17%) and Camphor (0.13%). Conclusion: The presence of these compounds is more likely to be responsible for the use of ginger in ethno medicine as in aromatherapy.